Microscopic features of chronic cheilitis - Sergei Nikolaevich Lebedev; Anna F. Solnyshkina; Oksana N. Guskova; Yuliya V. Lebedeva; Diana V. Marku; Olesya N. Skaryakina; Ivan S. Lebedev (Наука и инновации в медицине, 2025)
Aim – to evaluate morphological changes of the lip mucosa in chronic cheilitis: the condition of the epithelium, the microcirculation and the inflammatory infiltration of the intrinsic lamina of the mucosa.